Double-doped modified self-repairing and self-early-warning protective coating and preparation method thereof
By doping hydrotalcite-ginkgo leaf extract and lanthanide rare earth organic material modified low-surface coatings in the aqueous zinc-rich coating, a double-doped modified self-healing self-warning protective coating was formed, which solved the problem of shortening the coating life of the existing technology and the inability to achieve protective failure warning, and achieved better corrosion resistance and self-repair ability.
Patent Information
- Application Number
- CN202411782030.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
While the existing zinc-rich protective coatings improve cathode protection performance, they consume activated zinc too quickly, resulting in a shortening of the coating life and unable to achieve early warning of material protection failure.
Modified by doping hydrotalcite-ginkgo leaf extract (EGB-LDH) in an aqueous zinc-rich coating and composited with a modified low-surface treatment epoxy wear-resistant coating with lanthanide rare earth organic material, a double-doped modified self-healing self-warning protective coating was formed.
It improves the corrosion resistance and self-repairing ability of the coating, can easily identify the corrosion degree of the substrate through changes in fluorescence intensity, and extends the coating life.
Smart Images

Figure CN119570333A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of protective coatings, and in particular relates to a dual-doped modified self-repairing self-warning protective coating and a preparation method thereof. Background Art
[0002] The harm of corrosion to metal materials has always been an issue that cannot be ignored in industrial production and infrastructure maintenance. Metal corrosion not only affects the structure and performance of materials, but also poses a serious threat to the safety and life of equipment. One of the most effective means of corrosion prevention, ordinary coating systems have poor corrosion resistance and a short protection time. With the development of coating anti-corrosion technology, heavy-duty anti-corrosion system coatings are gradually used in engineering equipment protection. Heavy-duty anti-corrosion coating systems refer to a type of high-performance coatings with long-term protection in harsh corrosive environments. Commonly used coatings include polyurethane coatings, epoxy resin coatings, rubber coatings, zinc-rich coatings, etc., which are usually composed of primers, intermediate coatings, and topcoats. The film thickness is more than 200 µm. The coating composed of the three has an overall effect and the protection time can reach more than 15 years. Zinc-rich coatings, as a common anti-corrosion coating, are widely used in various corrosive environments for their simple operation and excellent anti-corrosion performance, and have become the main means of engineering facility protection. Among them, water-based zinc-rich coatings are highly praised for their low volatile organic content and environmental protection.
[0003] At present, the method for zinc-rich protective coatings is to dope carbon nanomaterials in zinc-rich coatings to improve their cathodic protection performance. The prior art document (CN 117070123 A) proposes a solvent-based zinc-rich heavy-duty anticorrosive coating, in which the flaky zinc powder, graphene oxide, flaky Mxene and flaky basalt components are all modified, which is beneficial to improve the compatibility and dispersibility of the coating, thereby effectively avoiding the delamination of the coating after construction. The flaky Mxene and graphene oxide are used as nano-scale fillers to improve the density of the coating. In addition, the flaky Mxene and graphene oxide can change the spatial structure of the coating to extend the corrosion path, increase the area of the protective layer in the film, make the slurry thixotropic, reduce the amount of solvent added, and help reduce the VOCs content of the coating. In addition, the flaky basalt is an inert filler with low oil absorption rate, which can reduce the addition of epoxy resin, thereby increasing the solid content of the dry film. Ultrafine flaky zinc powder can play a role in corrosion protection due to the cathodic protection effect. At the same time, the flaky structure of zinc powder makes the internal structure of the coating complex, delays the invasion of corrosive media, and can also improve the corrosion resistance of the coating. Use mixed active solvents instead of commonly used organic solvents. Mixed active solvents are reactive and can participate in the curing reaction of epoxy resins and become part of the cross-linked network of epoxy resins. Therefore, compared with volatile solvents, they can reduce solvent volatilization, reduce the VOCs content of the coating, and make the coating cure faster. However, the shortcoming of this prior art document is that the coating can only be improved by improving cathodic protection. Due to the increase in the number of activated zinc, the zinc consumption will be too fast, thus shortening the life of the coating. At the same time, it is impossible to directly determine the corrosion degree of the substrate through the surface of the coating, and thus it is impossible to achieve material protection failure warning.
[0004] Low surface energy coatings, also known as non-stick coatings, are a type of coating system that has developed rapidly in recent years. They are usually composed of fluorocarbon resins, silicone resins, polytetrafluoroethylene powders, special modified materials, etc. Low surface energy coatings are coatings prepared with low surface energy coatings. They have good adhesion to the substrate and a contact angle with pure water of >120°. As the technology of room temperature curing fluorocarbon resin coatings with excellent comprehensive properties such as ease of use and resistance to atmospheric aging gradually matures, new applications of low surface energy coatings continue to expand, playing an important role in marine engineering, national defense and military industry, friction reduction, anti-fouling, ice and snow sports, etc. Two-component, polyamine-cured low surface treatment epoxy coatings have the characteristics of low surface treatment, wear resistance and high solid content. They can be used specifically in areas where ideal surface treatment cannot or does not need to be achieved. They can provide long-term anti-corrosion protection in highly corrosive environments. They can be used as primers, intermediate paints, topcoats or single-coat coatings in atmospheric environments and immersion environments. They are suitable for properly treated carbon steel, galvanized steel, stainless steel, aluminum, concrete and many aged painted surfaces, and can be applied when the surface temperature is below 0°C. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to solve the deficiencies in the prior art and to provide a self-repairing and self-warning protective coating dual-doped with ginkgo leaf extract and rare earth complex and a preparation method thereof, wherein the water-based zinc-rich coating is modified by hydrotalcite-ginkgo leaf extract (EGB-LDH), the low-surface-treated epoxy wear-resistant coating is modified by lanthanide rare earth organic materials, and then the modified low-surface coating is compounded with the zinc-rich coating to obtain the dual-doped modified self-repairing and self-warning protective coating of the present invention.
[0006] Technical solution: The dual-doped modified self-repairing and self-warning protective coating described in the present invention is composited by a modified water-based zinc-rich coating and a modified low surface energy coating. The modified water-based zinc-rich coating is obtained by modifying the water-based zinc-rich coating with hydrotalcite-ginkgo extract, and the modified low surface energy coating is obtained by modifying the low surface energy coating with lanthanide rare earth organic materials.
[0007] Preferably, the weight content of the hydrotalcite-ginkgo extract in the modified water-based zinc-rich coating is 5%, and the weight content of the lanthanide rare earth organic material in the modified low surface energy coating is 5%.
[0008] Preferably, the hydrotalcite-ginkgo extract (EGB-LDH) is prepared by reacting ginkgo leaf extract and hydrotalcite.
[0009] Preferably, the lanthanide rare earth organic material is prepared from hydrated europium nitrate, 1-10 phenanthroline, terephthalic acid, anhydrous ethanol and deionized water.
[0010] Preferably, the preparation method of the EGB-LDH is as follows: adding the calcined hydrotalcite to a solution containing ginkgo extract and sodium hydroxide, stirring and controlling the pH of the mixed solution to be stable at 10.5-11.5, reacting at 50°C for 15-24h, filtering, washing to neutrality, and drying to obtain hydrotalcite-ginkgo extract.
[0011] Preferably, the components and contents of the modified water-based zinc-rich coating are as follows, by weight percentage: Zinc powder 60 - 80 1-Methoxy-2-propanol ≤10 Epoxy resin (MW700 - 1200) ≤5 Epoxy resin (MW<700) ≤5 γ-Glyceroloxypropyltrimethylsilane <5 Polyetheramine <10 EGB-LDH =5 Preferably, the components and contents of the modified low surface energy coating are as follows, in percentage by weight: Epoxy resin (MW<700) 20 C18-unsaturated fatty acids, dimer, polymer with 4,4'-(1-methylethylidene)biphenol and chloromethyloxirane 10 Nutshell liquid, polymer with epichlorohydrin 10 Xylene 10 Isobutanol 5 Methyl styrenated phenol 5 Styrenated phenol 5 1-Butanol 30 Lanthanide rare earth organic luminescent materials 5 The present invention also provides an application of a dual-doped modified self-repairing self-warning protective coating, comprising the following steps: 1) Spraying the modified water-based zinc-rich coating on the metal substrate through a spray gun and drying it; 2) Spraying the modified low surface energy coating onto the dried modified water-based zinc-rich coating of step 1) and drying it.
[0012] The spraying thickness of the modified water-based zinc-rich coating and the modified low surface energy coating is 50-90 μm.
[0013] Beneficial effects: The ginkgo leaf extract and rare earth complex dual-doped modified self-repairing and self-warning protective coating of the present invention has better corrosion resistance than general protective coatings; the water-based zinc-rich coating inside the coating is combined with EGB-LDH, and when the internal substrate is corroded, the external LDH releases the EGB, thereby promoting the formation of a corrosion-resistant passivation film inside the steel substrate and improving the self-repairing ability of the substrate itself; the low surface treatment epoxy wear-resistant coating on the outside of the coating provides efficient protection for the EGB-LDH water-based zinc-rich coating it covers by using its own high density, wear resistance and impermeability; the lanthanide metal organic luminescent material has a strong effect on the Fe inside the structure. 3+ The response is relatively sensitive. It is precisely by utilizing this characteristic that when the steel substrate protected by the coating is corroded, Fe 3+ As the concentration increases, the fluorescence intensity of the protective material decreases. From a macroscopic perspective, the degree of corrosion of the substrate can be identified by the change in luminescence intensity, without the need for more complicated detection equipment and methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the surface morphology (SEM) of the coating in Example 5 of the present invention before and after full immersion corrosion.
[0015] Figure 2 This is the surface morphology (SEM) of the basic water-based zinc-rich coating before and after full immersion corrosion. DETAILED DESCRIPTION
[0016] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with embodiments and drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.
[0017] Sources of some raw materials in the examples: Europium nitrate hexahydrate Ron's reagent, R003553 1,10-Phenanthroline National medicine o-phenanthroline 1,10-phenanthroline analytical pure GR chemical reagent Terephthalic acid Ron's reagent, R011713 CO3-LDH (Synthetic hydrotalcite) McLean's reagent, 11097-59-9 EGB Food Grade Ginkgo Leaf Extract Ginkgo Flavonoids Powder Water-based zinc-rich coating: Jotun Barrier 80 WF Low surface energy coating: Jotun coating, Jotamastic 90 Example 1 Preparation of lanthanide rare earth organic luminescent materials Europium nitrate hexahydrate, 1,10-phenanthroline g, and terephthalic acid were weighed and dissolved in anhydrous ethanol at a molar ratio of 1:2:1, stirred for 10 hours in a water bath at 80°C, and then centrifuged three times at a centrifugal rate of 5000 r / min; the mixed solution was placed in a reaction kettle and kept in an oven at 80°C for 24 hours to obtain a lanthanide rare earth organic luminescent material (Eu(PTA) 1.5 phen).
[0018] Example 2 Preparation of EGB-LDH The commercial CO3-LDH was placed in a muffle furnace by the calcination recovery method, calcined at 400℃ / 450℃ / 500℃ / 550℃ for 3h, and cooled to room temperature to obtain calcined LDH (CLDH). Then, 500mL of a mixture of 0.25mol / L EGB and 0.25 mol / L NaOH was prepared, and 2g CLDH was added to the mixture. During the stirring process, 2mol / L NaOH solution was added dropwise to control the pH of the mixture to stabilize at about 11, then nitrogen was passed for 20min, and the solution was sealed. Stir for 15h-24h in a 50℃ water bath, filter after stirring, wash the precipitate with deionized water and anhydrous ethanol to neutrality, and then dry at 60℃ to obtain EGB-LDH.
[0019] Example 3 Preparation of EGB-LDH modified water-based zinc-rich coating protective coating Pour the water-based zinc-rich coating (zinc powder 60wt%, 1-methoxy-2-propanol 10wt%, epoxy resin (MW700-1200) 5wt%, epoxy resin (MW<700) 5wt%, γ-glyceroloxypropyltrimethylsilane 5wt%, polyetheramine 10wt%) and EDH-LDH 5wt% into a mixer at a stirring speed of 700-1000 r / min. Stir thoroughly for 30 minutes to mix evenly. Spray the mixed EGB-LDH modified water-based zinc-rich coating on the steel substrate immediately with a spray gun. The thickness of the EGB-LDH modified water-based zinc-rich coating is controlled at 50-90µm. The sprayed coating is placed in an oven at 40°C for 2h.
[0020] Example 3-1 Preparation of EGB-LDH modified water-based zinc-rich coating protective coating Pour the water-based zinc-rich coating (zinc powder 70wt%, 1-methoxy-2-propanol 5wt%, epoxy resin (MW700-1200) 5wt%, epoxy resin (MW<700) 5wt%, γ-glyceroloxypropyltrimethylsilane 5wt%, polyetheramine 5wt%) and EDH-LDH 5wt% into a mixer at a stirring speed of 700-1000 r / min. Stir thoroughly for 30 minutes to mix evenly. Spray the mixed EGB-LDH modified water-based zinc-rich coating on the steel substrate immediately with a spray gun. The thickness of the EGB-LDH modified water-based zinc-rich coating is controlled at 50-90µm. The sprayed coating is placed in an oven at 40°C for 2 hours.
[0021] Example 4 Preparation of low surface energy coating modified by lanthanide rare earth organic luminescent material The low surface energy coating is prepared by fully stirring in a mixer for 15-20 minutes the epoxy resin (MW<700) content (MW<700), the polymer of C18-unsaturated fatty acid dimer, 4,4'-(1-methylethylidene)biphenol and chloromethyloxirane content (wt%), the polymer of nutshell liquid and epichlorohydrin content (wt%), xylene content (wt%), isobutyl alcohol content (wt%), methyl styrenated phenol content (wt%), styrenated phenol content (wt%) and 1-butanol content (wt%) for 15-20 minutes; the low surface energy coating having the above component contents can also be purchased.
[0022] Lanthanide rare earth organic luminescent material (Eu(PTA) 1.5 phen) 5wt% is poured into the dissolved anhydrous ethanol solution and poured into the mixer at a stirring speed of 700-1000 r / min. Stir thoroughly for 5-10 minutes to mix evenly. Finally, the low surface energy coating is mixed with Eu(PTA) 1.5 After the phen is mixed, slowly pour it into the blender and continue to stir rapidly for 15-20 minutes to mix evenly to obtain a lanthanide rare earth organic luminescent material modified low surface energy coating.
[0023] Example 5 Application method of dual-doped modified self-repairing self-warning protective coating The EGB-LDH water-based zinc-rich coating prepared in Example 3 was sprayed on the steel substrate by a spray gun, and the thickness of the water-based zinc-rich coating was controlled to be 50-90 μm. The sprayed coating was placed in an oven at 40° C. for 2 h. The lanthanide rare earth organic luminescent material-modified low surface energy coating prepared in Example 4 was sprayed on the EGB-LDH water-based zinc-rich coating by a spray gun, and the thickness of the coating was controlled to be 50-90 μm. The sprayed coating was placed in an oven at 40° C. for 6 h.
[0024] The ginkgo leaf extract and rare earth complex dual-doped modified self-repairing self-warning protective coating was prepared. The surface SEM morphology of the dual-doped modified self-repairing self-warning protective coating before and after full immersion corrosion is shown in the figure. Figure 1 As shown ( Figure 1 a is before corrosion, Figure 1 b is after corrosion), basic water-based zinc-rich coating before and after full immersion corrosion ( Figure 2 a is before corrosion, Figure 2 b (after corrosion) surface SEM morphology Figure 2 It is shown that the double-doped modified self-repairing self-warning protective coating prepared by the present invention has an increased overall density compared to the basic water-based zinc-rich coating, and the surface defects are reduced after immersion corrosion, which further reflects the improvement of the corrosion resistance of the coating.
[0025] Example 6 Method for conveniently identifying the degree of coating corrosion A handheld ultraviolet lamp was used to irradiate the ginkgo leaf extract and rare earth complex dual-doped modified self-repairing self-warning protective coating prepared in Example 5, and the samples before and after service were compared. From a macroscopic perspective, the change in fluorescence intensity was judged by human eye observation. If the fluorescence intensity was lower than that of the blank sample, it could be determined that corrosion occurred on the substrate.
[0026] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A dual-doped modified self-repairing self-warning protective coating, characterized in that: The modified water-based zinc-rich coating is composited with a modified low surface energy coating. The modified water-based zinc-rich coating is obtained by modifying the water-based zinc-rich coating with hydrotalcite-ginkgo extract, and the modified low surface energy coating is obtained by modifying the low surface energy coating with lanthanide rare earth organic materials.
2. The protective coating according to claim 1, characterized in that The weight content of the hydrotalcite-gingko extract in the modified water-based zinc-rich coating is 5%, and the weight content of the lanthanide rare earth organic material in the modified low surface energy coating is 5%.
3. The protective coating according to claim 1 and 2, characterized in that The hydrotalcite-gingko extract is prepared by reacting the ginkgo leaf extract and hydrotalcite.
4. The protective coating according to claims 1 and 2, characterized in that The lanthanide rare earth organic material is prepared from hydrated europium nitrate, 1-10 phenanthroline, terephthalic acid, anhydrous ethanol and deionized water.
5. The protective coating according to claim 3, characterized in that: The preparation method of the hydrotalcite-gingko extract is as follows: adding the calcined hydrotalcite to a solution containing the ginkgo extract and sodium hydroxide, stirring and controlling the pH of the mixed solution to be stable at 10.5-11.5, reacting at 50° C. for 15-24 hours, filtering, washing to neutrality, and drying to obtain the hydrotalcite-gingko extract.
6. The protective coating according to claim 1, characterized in that The components and contents of the modified water-based zinc-rich coating are calculated by weight percentage:
7. The protective coating according to claim 1, characterized in that The components and contents of the modified low surface energy coating are calculated by weight percentage:
8. Use of the protective coating according to any one of claims 1 to 7, characterized in that: The steps include: 1) Spraying the modified water-based zinc-rich coating on the metal substrate through a spray gun and drying it; 2) Spraying the modified low surface energy coating onto the dried modified water-based zinc-rich coating of step 1) and drying it.
9. The use of the protective coating according to claim 8, characterized in that: The spraying thickness of the modified water-based zinc-rich coating and the modified low surface energy coating is 50-90 μm.
Citation Information
Patent Citations
Para aminobenzoic acid root cutting layer hydrotalcite material modified rebar epoxy resin coating and preparation method thereof
CN109096865A
Antistatic paint for surface of high-voltage insulating medium and preparation method
CN109096867A
Green health-care environmentally-friendly coating and preparation method thereof
CN109608988A
Method and application for ginkgo leaf synthesized and modified Fe-Co duplex metal particles
CN109773208A
Self-corrosion-resistant water-based organic zinc-rich coating and preparation method thereof
CN114410186A